Standardisasi Klusterisasi UMKM untuk Mendukung Ketepatan Kebijakan Pemberdayaan: Studi pada UMKM Binaan DJPb - Marsandhi Evan Pardede; Lyssa Zulya Zalyra (Direktorat Sistem Perbendaharaan, 2026)
Unlike previous studies that generally classify Micro, Small, and Medium Enterprises (MSMEs) based on mathematical patterns without directly linking them to government policy frameworks, this study aims to develop a simple MSME clustering model that is aligned with the classification outlined in the Technical Guidelines of the Directorate General of Treasury. Data were collected through a questionnaire consisting of 21 questions designed to classify MSMEs into three categories: start-up, independent, and export-ready enterprises. The study employed a purposive sampling technique involving 360 assisted MSMEs in West Sumatra. The decision tree method was employed in this study because it is capable of generating structured classification rules that are easy to understand and interpret by policymakers. The results indicate that the initial 21-question instrument can be simplified into nine key questions related to business structure, taxpayer identification number (NPWP) ownership, production technology, product standards, export procedures, business licensing, annual tax return reporting, marketing platforms, and business contracts. This simplification improves the efficiency of the clustering process without compromising its alignment with the existing policy framework. Relevant government agencies may consider adopting this decision tree model as a standard for MSME clustering, as it is simpler, more practical, and easier to implement in supporting MSME development and capacity-building programs.